Biological aspects of pollen development in six species of Brassicaceae - S. Nasser, Naji; A.Manfy, Enas (Iraqi Journal of Science, 2023)
The present investigation revealed cytological variations for six species (Erucasativa, Sisymbirium irio, Diplotaxis harra, Erucaria hispanica, Schimpera Arabicaand Brassica tournefortii ) belong to the Brassicaceaefamily.The flower buds werecollected from Al-Habania lake that located in Al-Anbar-Iraq. Using ironacetocarminesquash technique in anther-smear studies which revealed achromosomal anomalies such as Lagging/brddge chromosomes, Micronuclei &initiated delay of four daughter cells.The frequency of abnormalities ranged (0.04 -0.77%) which indicated the unstable heredity source of most wildplants. The pollengrains viability was estimated using acetocarmine stain, viable grains had stained,while sterile grains had not.The biostatic analysis revealed a high significant deference at >0.01 due to the highest numbers of viable pollen grains compared with sterility. Pollen charactersof polar and equatorial view are significantly sufficient for classified characterization of the plant species. An interesting correlationratio of P/E to estimate pollen grain shape, in Brassicaceae polar view was spheroidal three grooves of all species , wide elliptical shape or sub spheroidal in equatorial view, and grains size were medium. The study conclusion that all six species have high productivity of viable pollen grains which confer resistance to environment, therebymeiotic irregularities could be induced unstable genetic resources andsterility.